Effects of Li2O-B2O3-SiO2 glass on the low-temperature sintering of Zn0.15Nb0.3Ti0.55O2 ceramics. Issue 7 (May 2018) - Li, Enzhu; Yang, Hongcheng; Yang, Hongyu; Zhang, Shuren
Abstract: The influences of Li2 O-B2 O3 -SiO2 glass (LBS) on the activation energy, phase composition, the stability of the structure and microwave dielectric properties of Zn0.15 Nb0.3 Ti0.55 O2 ceramics have been systematically investigated. LBS glass acted as flux former and contributed to the reactive liquid-phase sintering mechanism, which remarkably lowed the sintering temperature from 1150 °C to 900 °C and enhanced the shrinkage and densification of ceramic at the low sintering temperatures. The ceramics with 1.5 wt% LBS glass sintered at 900 °C for 3 h show great properties: ε r = 73.59, Q × f = 8024 GHz, τ f = 270.54 ppm/°C.